Cost analysis of community scale smokeless charcoal briquette productio from agricultural and forest residues - K. Y. Tippayawong (2019)
© 2019 The Authors. Published by Elsevier Ltd. Biomass conversion by carbonization process is a simple and appropriate method to convert agricultural and forest residues into solid bio-renewable fuel. Great attentions have been paid to commercial smokeless charcoal production especially those in rural communities where large amount of agricultural and forest residues are available and not yet harnessed. Besides, smokeless charcoal is a premium product with stable export demand, generating better value added than normal charcoal. In the present paper, a biomass residues-to-smokeless charcoal conversion plant with appropriate thermal technology was proposed for a local municipality in Mae Hong Son, Thailand. Cost analyses as well as an economic feasibility survey were carried out to evaluate potential benefits of the proposed venture. The study was about utilizing biomass residues available around Mae Hong Son area. The site was firstly chosen based on available supply, using basic supply consolidation models. Charcoal from these biomass residues were prepared, and compacted into charcoal briquettes, and thermally treated to produce final product as smokeless charcoal briquettes. This study focused on the feasibility of demand, engineering, and financial concern. Finally, the biomass conversion model was established together with a practical cost model which could be useful to investors and entrepreneurs for decision making in commercializing community scale production of smokeless charcoal.